SISTEM INFORMASI ADMINISTRASI PERTANAHAN (STUDI KASUS KECAMATAN CISARUA KABUPATEN SUMEDANG) - Atep Ruhiat (Journal Of Regional Public Administration (JRPA), 2016)
E-government is the central information system of governance, with the system integration of data and information can be quickly managed and administered. So that the administration would be considered better. However, in the implementation of new e-government development in the central government only, while the real root of the central government, the village government to district technology is still unspoiled. So should the implementation of an integrated information system was also built scaled village and district administration. Cisarua subdistrict located in Sumedang trying to build an information system related teintegrasi land. The background of the problem, namely the cadastral data in each village have not been archived properly so hard on the monitor by the district. Therefore this research is to integrate the data of land in each village in the district of Sumedang Cisarua. The end result, which made a land administration information system based websites.